THE ABILITY TO WRITE POETRY ON IIS-2 GRADE X STUDENT OF PRIVATE SMA NURUL IMAN TANJUNGMORAWA IN ACADEMIC YEAR 2019/2020 - br tarigan, fitri sanny; Hutagalung, Trisnawati (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2021)
This study aims to analyze the ability to write poetry in class X IIS-2 SMA Private Nurul Iman Tanjungmorawa in the 2019/2020 academic year. The method used in this research is descriptive method. The population of this study were all students of class X SMA Private Nurul Iman Tanjungmorawa which consisted of 4 classes with a total of 111 students. Sampling was done by means of random sampling technique (random) and selected class X IIS-2 with a total of 25 students. The research instrument used was an essay test. The essay test in question is writing poetry by paying attention to the building blocks of poetry. The results showed that the ability to write poetry based on theme suitability with an average score of 100, diction / choice of words with an average score of 79, images / images with an average score of 53, use of figure of speech / language style with an average score of 47, and the mandate of the average score is 100. So the results show that the students of class X IIS-2 SMA Private Nurul Iman Tanjungmorawa are categorized as quite capable of writing poetry with the average score of the five aspects of the assessment is 75.8 and in the sufficient category.Key Words: Ability, Write, Poetryaspects of the assessment is 75.8 and in the sufficient category.